A child-focused version of the Attention Network Task designed to investigate interactions between the attention networks, including the endogenous orienting network. Issue 5 (3rd July 2020) - Johnson, Katherine A.; Lewis, Frances C.; Cornish, Kim M.
ABSTRACT: A new variation of the Attention Network Task (ANT) was designed to measure the functioning of and interactions between the alerting, exogenous and endogenous visual spatial orienting, and executive control systems in young school children. Previous research has produced mixed results regarding typical functioning of the attention networks in six-year-olds; no ANT has measured the functioning of the endogenous network. This Staged ANT tested the Alerting, Exogenous, and Endogenous orienting networks in separate conditions. Two hundred and forty-seven children (average age 6 years, 103 girls) completed the task. There was no clear benefit of the alerting cue until the spatial orienting cues were introduced into the task, suggesting task complexity was needed before alerting benefits were observed. The validity effect of the exogenous cue was very strong: in contrast, the validity effect of the endogenous cue was very weak. The flanker effect was very strong. A benefit of the alerting cue was shown during both the exogenous and endogenous conditions, while a cost of the alerting cue was shown during the invalid exogenous trials. Neither the alerting nor validity effects interacted with the flanker effect. These results suggest that the alerting cue primes the exogenous and endogenous systems for the upcoming cues. Once the complexity of the task increases with the addition of the flankers, the alerting effect attenuates. The alerting and the two orienting networks interact together but the executive attention network acts independently, in children aged 6 years.